OVERWEIGHT AND OBESITY AMONG CHILDREN AGED 6 TO 10, ENROLLED IN A PUBLIC STATE SCHOOL IN CAMPO GRANDE MS (Fiep Bulletin - online, 2013)
The main aim of this study was to diagnose the percent of overweight and obesity among 6 to 10 year-old children in a public state school in Campo Grande MS. This research specifically tried to analyse the sex differences. The sample was made of 315 children aged from 6 to 10, which were 176 girls and 139 boys. The anthropometric (weight and height) was adopted as a research technique, using the formula BMI=weight/height2 to identify the Body Mass Index (BMI). The results show that 30,1% of the studied group have high indices of body mass, 21,9% of this group with overweight and 8,5% with obesity. It was concluded that the researched sample shows higher percents of body mass excess (overweight and obesity), and action must be taken in order to ease this problems still on the childhood, as, if it goes on the adult age, the consequences will be even worst.
Keywords: Childhood; Body Mass Excess; Health